2022
DOI: 10.1084/jem.20220759
|View full text |Cite|
|
Sign up to set email alerts
|

Monocyte-derived macrophages aggravate pulmonary vasculitis via cGAS/STING/IFN-mediated nucleic acid sensing

Abstract: Autoimmune vasculitis is a group of life-threatening diseases, whose underlying pathogenic mechanisms are incompletely understood, hampering development of targeted therapies. Here, we demonstrate that patients suffering from anti-neutrophil cytoplasmic antibodies (ANCA)–associated vasculitis (AAV) showed increased levels of cGAMP and enhanced IFN-I signature. To identify disease mechanisms and potential therapeutic targets, we developed a mouse model for pulmonary AAV that mimics severe disease in patients. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…Pharmacological inhibition of STING activation prevented the manifestation of this disease. In the same line it was published that the progression of ANCA-associated vasculitis is dependent on activation of cGAS/STING/IRF3 axis (Kessler et al, 2022). Blockade of STING activation improved the severity of this disease significantly.…”
Section: Discussionmentioning
confidence: 84%
“…Pharmacological inhibition of STING activation prevented the manifestation of this disease. In the same line it was published that the progression of ANCA-associated vasculitis is dependent on activation of cGAS/STING/IRF3 axis (Kessler et al, 2022). Blockade of STING activation improved the severity of this disease significantly.…”
Section: Discussionmentioning
confidence: 84%
“…Vibratome sections of lungs 2 days after infection were analysed as previously described [9]. Briefly, mice were humanely killed by xylazine/ ketamine overdose and lungs inflated with 1 ml of 2% low melting temperature agarose (Promega, US) at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The ITR structure of the AAV genome may activate cytoplasmic DNA receptors. Studies have demonstrated that rAAV can induce cGAS and antiviral genes such as TNF-α and IFN-γ [ 105 ]. The ITR, located at either end of the AAV or within the bidirectional promoter, can generate reverse complementary positive-strand RNA and negative-strand RNA.…”
Section: Aav Vector Therapymentioning
confidence: 99%
“…Then, TLRs activate NF-κB and IRF7 via MyD88 signaling pathway, this activation ultimately regulates the production of IFN-I and ISGs [ 13 , 103 , 104 ]. (B) The ITR structure of the AAV genome may activate cytoplasmic DNA to induce cGAS and antiviral genes and activate the cGAS-STING signaling pathway [ 105 ]. (C) Due to the promoter activity of the ITR of AAV, AAV may form dsRNA in target cells and trigger the RIG-I/MDA5-mediated RLR-MAVS innate immune signaling pathway [ 83 , 106 ].…”
Section: Figurementioning
confidence: 99%